La précarité : une relation entre travail, organisation et santé - D'Amours, Martine (Relations industrielles / Industrial Relations, 2010)
The article reviews the book, "La précarité : une relation entre travail, organisation et santé," edited by Gilbert de Terssac, Corinne Saint-Martin and Claire Thébault.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z